Pengembangan Multimedia Interaktif Hukum Kekekalan Momentum Sudut Menggunakan Macromedia Flash Pada Siswa Kelas XI - Farouq Hussein; Abdurrahman Abdurrahman; Agus Suyatna (Jurnal Pembelajaran Fisika, 2018)
The purpose of this development research is to produce interactive multimedia on the material of angular momentum conservation law and describe the attractiveness, ease, usefulness, and effectiveness of the product. This interactive multimedia development research begins with a needs analysis, formulating learning objectives, formulating material points, formulating a measuring instrument, making an initial script, making a product, then testing the feasibility of design and material carried out by design experts and material experts, followed by one on one tests. After being revised, the product was field tested which was carried out in class XI SMA N 07 Bandar Lampung. The results of the field trials carried out showed that multimedia had an interesting score of 3.04 (interesting), an ease score of 2.89 (quite easy), and a score of the usefulness of 2.99 (quite useful). The test also includes the effectiveness of the product, and the result is that products that are developed effectively are used as learning media seen from student learning outcomes, namely 84% of students have completed the KKM. The conclusion of this development research is interactive multimedia on a physics learning material angular momentum conservation law is appropriate to be used as a learning medium needs to contain concepts, principles, formulas, simulations, videos, and tests.Tujuan dari penelitian pengembangan ini adalah menghasilkan multimedia interaktif pada materi hukum kekekalan momentum sudut, serta mendeskripsikan kemenarikan, kemudahan, kemanfaatan, dan keefektifan produk. Penelitian pengembangan multimedia interaktif ini menggunakan model pengembangan Sadiman yang telah dimodifikasi dengan menambahkan langkah evaluasi. Hasil Uji coba lapangan yang dilakukan menunjukkan bahwa multimedia memiliki skor kemenarikan 3,04 (menarik), skor kemudahan 2,89 (cukup mudah), dan skor kemanfaatan 2,99 (cukup bermanfaat). Uji yang dilakukan juga meliputi keefektifan produk, dan hasilnya adalah produk yang dikembangkan efektif digunakan sebagai media pembelajaran dilihat dari hasil belajar siswa, yaitu 84% siswa telah tuntas KKM. Kesimpulan dari penelitian pengembangan ini adalah multimedia interaktif pada pembelajaran fisika materi hukum kekekalan momentum sudut layak digunakan sebagai suatu media pembelajaran. Multimedia interaktif yang dibuat perlu bermuatan konsep, prinsip, formula, simulasi, video, dan tes.Kata kunci: pengembangan, multimedia interaktif, hukum kekekalan momentum sudut, macromedia flash.